Suppression of the Verwey Transition by Charge Trapping. Issue 3 (26th February 2018) - Schmitz‐Antoniak, Carolin; Schmitz, Detlef; Warland, Anne; Darbandi, Masih; Haldar, Soumyajyoti; Bhandary, Sumanta; Sanyal, Biplab; Eriksson, Olle; Wende, Heiko
Abstract: The Verwey transition in Fe3 O4 nanoparticles with a mean diameter of 6.3 nm is suppressed after capping the particles with a 3.5 nm thick shell of SiO2 . By X‐ray absorption spectroscopy and its associated X‐ray magnetic circular dichroism this suppression can be correlated to localized Fe 2+ states and a reduced double exchange visible in different site‐specific magnetization behavior in high magnetic fields. The results are discussed in terms of charge trapping at defects in the Fe3 O4 / SiO2 interface and the consequent difficulties in the formation of the common phases of Fe3 O4 . By comparison to X‐ray absorption spectra of bare Fe3 O4 nanoparticles in course of the Verwey transition, particular changes in the spectral shape could be correlated to changes in the number of unoccupied d states for Fe ions at different lattice sites. These findings are supported by density functional theory calculations. Abstract : The suppression of the Verwey transition by silica capping of 6 nm magnetite nanoparticles is investigated by X‐ray absorption spectroscopy and correlated to localized Fe 2+ states at the interface demonstrating the crucial role of the electronic structure for the Verwey transition. A reduced double exchange revealed by different site‐specific spin canting behavior as well as changes in the electronic structure support this finding.